Problems of China s Rural Financial System - Wang, Ruixiang; Liu, Xinmin (MTT, 2005)
There are three different kinds of rural financial institutions in China: commercial banks Agricultural Bank of China (ABC); a policy-based bank Agricultural Development Bank of China (ADBC); and many co-operative financial institutions with well-developed village networks Rural Credit Co-operatives (RCCs). Although there are many rural financial institutions in China, most of the farmers can only obtain loans through informal channels, especially from loan sharks. Obviously China s rural financial system does not work well. The two major problems of the system are: substantial deposits of farmers flowing out into urban areas; and formal financial institutions denying loans to poor rural households usually because they lack collateral and are faced with a riskier environment. Some suggestions for the reform on rural financial system are put forward here: to reinforce the agriculturesupporting role of the policy-based finance; to retain enough commercial finance in rural areas; to reform RCCs and diversify grassroots rural financial institutions; and prevent farmers to obtain loans from the wrong sources.
Keywords: Ys; rural financial system; rural financial institutions; rural credit cooperatives; microfinance